Evaluation of Intraocular Pressure by Ocular Response Analyzer in Patients Undergoing Hemodialysis. Issue 4 (April 2016) - Yuksel, Nilay; Duru, Necati; Uz, Ebru; Mutlu, Melek; Altinkaynak, Hasan; Ozen, Umut; Turkyilmaz, Mustafa; Cagil, Nurullah
Abstract : Purpose: The aim of this study was to compare the biomechanical parameters of the cornea and intraocular pressure (IOP) before and after hemodialysis (HD) in patients with end-stage renal disease (ESRD) and also healthy subjects. Materials and Methods: Twenty-one patients with ESRD undergoing HD treatment (study group) and 21 healthy individuals (control group) were enrolled in this prospective study. Right eyes of each subjects were included. Central corneal thickness (CCT) were measured using Sirius Scheimpflug camera. Corneal hysteresis (CH), corneal resistance factor (CRF), corneal-compensated IOP (IOPcc), and Goldmann-related IOP (IOPg) were measured using ocular response analyzer. In the study group, measurements were taken just before HD and 30 minutes after HD. Results: The mean CCT, CRF, IOPg values did not differ between pre-HD, post-HD, and controls ( P >0.05). CH was found to be significantly higher in control group (10.6±1.2 mm Hg) when compared with pre-HD (8.07±1.8 mm Hg) and post-HD (8.8±1.6 mm Hg) CH values ( P =0.0001). The mean IOPcc values did not differ pre-HD (18.5±3.5 mm Hg) and post-HD (17.8±3.9 mm Hg) ( P =0.39). The mean IOPcc values were lower significantly in control group (15.4±2.8 mm Hg) when compared with pre-HD and post-HD values ( P =0.02 and 0.02, respectively). Significant correlations were seen between post-HD CRF and post-HD CCT ( r =0.6, P =0.03); and post-HD IOPg and post-HD CCT ( r =0.51, P =0.01). Conclusions: ESRD may disrupt the biomechanical properties of the cornea. Changes in ocular response analyzer parameters should be kept in mind to evaluate accurate IOP measurements in patients with ESRD.